The Establishment Of Student Characters In The Pandemic Time Covid-19 Through Al-Islam And The Kemuhammadiyahan (AIK) - Yusutria Yusutria; Yuzarion Yuzarion; Nisa Amalia Kholifah; Yasmin Syarifah al-Husna; Ikhsan Alfikri; Rina Febriana (At-Tarbiyat, 2021)
The condition of the Covid-19 pandemic is a challenge to the Indonesian education world to strengthen the nation's character education, especially Al-Islam and Muhammadiyah teachers (AIK), which will provide opportunities for students to practice character values ​​in society. Research using qualitative. Data collection came from observations, accompanied by notes about the state or behavior of the target object, comments, interviews were shown to the principal and AIK teachers as many as three people, and documentation. Data analysis techniques include data reduction, presentation, verification, and conclusion. The results of research on the role of teachers in shaping student character during the Covid-19 pandemic, namely teachers must understand their duties and functions, adhere to SOP procedures, use online and blended learning methods, collaborate with parents based on SOPs in the use of social media and distribute character control sheets to students and parents. The obstacles are applying health protocols, limited time duration, internet access, internet support, mastery of technology owned by teachers and parents and students, media abuse among students, and lack of parental monitoring due to parents' busy earning a living. Patience from students, parents are asked to do the tasks that are assigned to the child.